2018
DOI: 10.3389/fneur.2018.00078
|View full text |Cite
|
Sign up to set email alerts
|

Non-Verbal Cognitive Abilities in Children and Adolescents Affected by Migraine and Tension-Type Headache: An Observational Study Using the Leiter-3

Abstract: Headache is one of the most common neurological disorders in developmental age. Several studies investigated the relationship between headache and emotional/behavioral problems. We studied non-verbal cognitive abilities, including non-verbal memory and attention skills, in order to evaluate the impact of primary headache on these domains. The latest version of the cognitive battery Leiter International Performance Scale – Third Edition (Leiter-3), a non-verbal test, was administered to 35 children and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In disagreement with previous studies, Margari et al ( 39 ) reported the absence of significant differences between patients with primary headache and controls in “Forward Memory,” “Reverse Memory” and “Non-verbal Memory” subtests scores, issued from the cognitive non-verbal test “Leiter-3” ( 57 ). However, the study described a significant association of frequency of the attacks and headache disability with non-verbal memory abilities, suggesting that higher headache disability may have a significant impact on specific cognitive domains, such as the non-verbal memory.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In disagreement with previous studies, Margari et al ( 39 ) reported the absence of significant differences between patients with primary headache and controls in “Forward Memory,” “Reverse Memory” and “Non-verbal Memory” subtests scores, issued from the cognitive non-verbal test “Leiter-3” ( 57 ). However, the study described a significant association of frequency of the attacks and headache disability with non-verbal memory abilities, suggesting that higher headache disability may have a significant impact on specific cognitive domains, such as the non-verbal memory.…”
Section: Resultsmentioning
confidence: 81%
“…In particular, comparing the performance of children suffering from migraine with (n. 17) and without aura (n. 31), the authors did not identify significant differences in the distribution of Progressive Matrices scores between the groups of patients. In a more recent study, Margari et al evaluated the non-verbal intelligence abilities, including fluid intelligence, attention skills and non-verbal memory, in pediatric patients with primary headache ( 39 ). Thirty-five children suffering from migraine (n. 26) or TTH (n. 9) and 23 healthy subjects were evaluated with the cognitive battery “Leiter-3” ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of enrollment children were 3-11 years old, had normal hearing in both ears (i.e., 25 dB HL or better at 0.5, 1.0, 2.0, and 4.0 kHz), no history of exposure to traumatic noise, and normal tympanometry. Children with a history of mental illness, neurological disease, or loss of consciousness were excluded, as these factors impact performance on CATs [19][20][21] . HIV status was con rmed in children using medical records or a rapid HIV test and recon rmed using an ELISA assay.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Our own research group came to similar conclusions (68). Of the most recent studies, Margari and colleagues showed that both migraine and tension-type headache affect non-verbal cognitive abilities in children and adolescents (9). Termine and co-workers, themselves corroborating the presence and seriousness of the problem in their review, add that “…migraine-related cognitive deficits may interfere with functioning levels across several settings”, and suggest that “[a] careful analysis of cognitive impairment in the context of migraine is pivotal for making informed decisions on the most appropriate care pathways” (10).…”
Section: Introductionmentioning
confidence: 99%